Range of motion of resistance exercise affects the number of performed repetitions but not a time under tension - Michał Krzysztofik (Nature Portfolio, 2021)
Abstract The resistance training volume along with the exercise range of motion has a significant impact on the training outcomes. Therefore, this study aimed to examine differences in training volume assessed by a number of performed repetitions, time under tension, and load–displacement as well as peak barbell velocity between the cambered and standard barbell bench press training session. The participants performed 3 sets to muscular failure of bench press exercise with the cambered or standard barbell at 50% of one-repetition maximum (1RM). Eighteen healthy men volunteered for the study (age = 25 ± 2 years; body mass = 92.1 ± 9.9 kg; experience in resistance training 7.3 ± 2.1 years; standard and cambered barbell bench press 1RM > 120% body mass). The t-test indicated a significantly higher mean range of motion for the cambered barbell in comparison to the standard (p < 0.0001; ES =  −2.24). Moreover, there was a significantly greater number of performed repetitions during the standard barbell bench press than cambered barbell (p < 0.0001) in a whole training session, while no difference was found in total time under tension (p = 0.22) and total load–displacement (p = 0.913). The two-way repeated-measures ANOVA indicated a significant barbell × set interaction effect for peak velocity (p = 0.01) and a number of repetitions (p = 0.015). The post-hoc analysis showed a significantly higher number of repetitions for standard than cambered barbell bench press in set 1 (p < 0.0001), set 3 (p < 0.0001) but not in set 2 (p = 0.066). Moreover, there was a significantly higher peak velocity during the cambered than standard barbell bench press in set 1 (p < 0.0001), and set 2 (p = 0.049), but not in set 3 (p = 0.063). No significant differences between corresponding sets of the standard and cambered barbell bench press in time under tension and load–displacement were found. However, concentric time under tension was significantly higher during cambered barbell bench press in all sets (p < 0.05) when compared to the standard barbell bench press, while eccentric time under tension was significantly lower during the cambered than standard barbell bench presses only in the set 3 (p = 0.001). In summary, this study briefly showed that measuring training volume by the number of performed repetitions is not reliable when different exercise range of motion is used.